Self-mutilation in adolescence and school life: an integrative literature review (Educação e Pesquisa, 2023)
The aim of this study consists of revising academic productions published over the last ten years regarding self-mutilation in adolescence and its repercussions for school life. The methodology employed was the integrative literature review, gathering papers from Scielo and Scopus database. As a result, 13 papers were highlighted, which were analyzed through the following categories: i) the teacher’s perspective, based on the challenges faced and the contributions from the school environment in self-injury cases; and ii) triggering factors related to self-injury. It can be concluded that for the teenagers the act of self-injuring is a way of communicating with themselves and with others, being at once a lonely move but also a sign of the psychological suffering they are experiencing, which can be observed and lived in a variety of ways. The words, gestures, experiences and actions in a whole, individual or collective, are considered as factors that can either promote acceptance of their psychological issues or can lead them to injure themselves. Regarding this, the teacher and family’s perception has become an important movement, in the teenagers’ perspective, because both possess conditions to help the teenagers in this issue, offering support, assistance, care and listening, essential so that they could face the troubled period they are going through.